Toward a Functional Annotation of the Human Genome Using Artificial Transcription Factors - Lee, Dong-ki; Park, Jin Woo; Kim, Youn-Jae; Kim, Jiwon; Lee, Yangsoon; Kim, Jeonglim; Kim, Jin-Soo

(untitled) (Genome Research, 2003)
We have developed a novel, high-throughput approach to collecting randomly perturbed gene-expression profiles from the human genome. A human 293 cell library that stably expresses randomly chosen zinc-finger transcription factors was constructed, and the expression profile of each cell line was obtained using cDNA microarray technology. Gene expression profiles from a total of 132 cell lines were collected and analyzed by (1) a simple clustering method based on expression-profile similarity, and (2) the shortest-path analysis method. These analyses identified a number of gene groups, and further investigation revealed that the genes that were grouped together had close biological relationships. The artificial transcription factor-based random genome perturbation method thus provides a novel functional genomic tool for annotation and classification of genes in the human genome and those of many other organisms.